Producing a sweetened drink for diet using invertase enzyme extracted from some Iraqi dates - Al-Garawi, Zahraa Salim; Ahmed, Ahmed Riyad; Hussein, Ahmed Mohammed; Nasir, Naba` Sabah (Journal of natural sciences, life and applied sciences, 2023)
This research was conducted at the Department of Chemistry at Mustansiriyha University, to prepare a diet sweetie syrup for baking with no chemical additives.  To achieve this aim, the activity of the enzyme invertase was determined in four types of Iraqi dates. By environmentally friendly method, the sugar solution was prepared from four types of dates (Khastawi, Ashrassi, Barhi, and Zuhdi) by crushing the dates and separating the mixture using a centrifuge. The crude enzyme was extracted and the solution was characterized using high-performance liquid chromatography HPLC. The enzymatic activity of the crude invertase enzyme was measured using the chemical method. The results showed a high activity of the invertase enzyme in all the studied types of dates, but the highest activity of the enzyme was in Barhi dates (0.072) units / kg, and the lowest activity was in Khastawi type (0.051) units / kg. There were percentage of monosaccharides in all types of dates but disaccharides appeared in Al-Barhi, Al-Zuhdi, and Al-Ashrasi only. The enzymatic solution of Al- Barhi was used to prepare a natural sweetened syrup by mixing with sucrose solution. The results of the qualitative test indicated di saccharide before adding the enzymatic solution and only monosaccharides after adding the enzymatic solution, which referred to a successful sweetie syrup. In a conclusion, invertase activity in dates is depending on the type of date, and that a natural sweetened syrup for drinking or eating can be easily and successfully prepared from date extract without chemical additives.
Keywords: invertase enzyme; Iraqi dates; high-performance liquid chromatography technique; sucrose